Frequency dependence of the relaxor-to-ferroelectric transition under applied electrical and mechanical fields. Issue 4 (April 2019) - Martin, Alexander; Khansur, Neamul H.; Riess, Kevin; Webber, Kyle G.
Abstract: Relaxor ferroelectrics are a unique material class with underlying microscopic processes that are yet to be fully understood. In particular, the electrical and mechanical field-modulated transition from the relaxor state to long-range ferroelectric order has been found to be the origin of the large unipolar strain response in some lead-free ferroelectric systems. Importantly, the dynamics of this transition are different than the domain wall nucleation and growth found in normal ferroelectrics, significantly changing the frequency response. In this study, the electromechanical behavior of a (Na1/2 Bi1/2 )TiO3 -based lead-free relaxor ferroelectric is shown under applied external mechanical and electric field over several orders of magnitude in loading rate. Depending on the loading history, it is possible to directly investigate both the relaxor-to-ferroelectric transition as well as domain wall motion in the same sample. These data demonstrate the variations in frequency response between these nonlinear hysteretic processes.